Database processing : fundamentals, design, implementation - Kroenke, David M.; Dolan, Kathleen A. (Chicago : Science Research Associates, 1988)
Today, database processing is fast becoming the rule for the development of new computer applications.
Includes index.
Includes bibliographical references: p. 675-679.
II 15/01/2019
Loans
Keywords: Database management